2021
DOI: 10.1088/1748-9326/abf3da
|View full text |Cite
|
Sign up to set email alerts
|

Comment on ‘Changes of inundation area and water turbidity of Tonle Sap Lake: responses to climate changes or upstream dam construction?’

Abstract: Recent hydropower development in the Mekong River has triggered a lot of discussion about its impact on flood dynamics along the river, as well as in one of the world’s most productive lake-floodplain systems—the Tonle Sap Lake. A recent article by Wang et al (2020 Environ. Res. Lett. 15 0940a1) in this journal conclude that changes in precipitation have played a much larger role than the operation of hydropower dams, contradicting existing research. However, we argue that by using an annual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
2
11
0
Order By: Relevance
“…The return period of the inundation area was estimated using the Gumbel distribution only showed no trend in either of the two periods (Figure 9 This study showed significant decreasing trends of water levels and inundation areas from the late 1990s in the dry season and annual scales (Figure 3). This is in line with previous studies (Kallio & Kummu, 2021;Lin & Qi, 2017;Wang et al, 2020;Wang et al, 2021), indicating a substantially diminished flood pulse of the TSL from 2000. Existing literature based on remote sensing data and other resources have limited with the available time series of water level and inundation area data from the late 1980s (Dang et al, 2016;Ji et al, 2018;Sakamoto et al, 2007;Tangdamrongsub et al, 2016), but our study provides a more extended time period analysis and puts the flood pulse change to the TSL since the late 1990s into a longer time perspective.…”
Section: Anthropogenic Impacts On the Flood Pulsesupporting
confidence: 93%
See 2 more Smart Citations
“…The return period of the inundation area was estimated using the Gumbel distribution only showed no trend in either of the two periods (Figure 9 This study showed significant decreasing trends of water levels and inundation areas from the late 1990s in the dry season and annual scales (Figure 3). This is in line with previous studies (Kallio & Kummu, 2021;Lin & Qi, 2017;Wang et al, 2020;Wang et al, 2021), indicating a substantially diminished flood pulse of the TSL from 2000. Existing literature based on remote sensing data and other resources have limited with the available time series of water level and inundation area data from the late 1980s (Dang et al, 2016;Ji et al, 2018;Sakamoto et al, 2007;Tangdamrongsub et al, 2016), but our study provides a more extended time period analysis and puts the flood pulse change to the TSL since the late 1990s into a longer time perspective.…”
Section: Anthropogenic Impacts On the Flood Pulsesupporting
confidence: 93%
“…The apparent differences in the trend between the observed and simulated discharges at Stung Treng station (Figure 9) suggested the potential impacts of hydropower development on discharges in the Mekong mainstream and flood pulse parameters in the TSL. Kallio and Kummu (2021) also…”
Section: Anthropogenic Impacts On the Flood Pulsementioning
confidence: 97%
See 1 more Smart Citation
“…However, whether the reduction is caused by upstream dams, climate or local operations is hotly debated. For instance, the claim that Chinese dams have minimal impact on the inundation area of the Tonle Sap by Wang et al (2020) was refuted in a response letter by Kallio and Kummu (2021). To investigate these competing drivers, we compared the reduction of wetseason discharge across various stations.…”
Section: Impacts Of Upstream Dams and Precipitationmentioning
confidence: 99%
“…The Tonle Sap Lake has been decreasing in size throughout the years (Sect. 4.2.2; Kallio and Kummu, 2021;Wang et al, 2020). A parallel can be drawn with Poyang Lake in Yangtze River.…”
Section: Wider Environmental Implicationsmentioning
confidence: 99%